Indonesia's Public Diplomacy Attempt in the Indonesian eSports Ecosystem 2014-2022. - Putra, Putu Krisyudea Dafara; Kurnia Putri, Penny; Kawitri Resen, Putu Titah (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 3 No 2 (2024): JURNAL DIKSHI, 2024)
This research aims to describe Indonesia's public diplomacy efforts in developing Indonesia's eSports ecosystem in 2014-2022 using qualitative research methods. This study uses the framework of the concept of public diplomacy. eSports, which originally came from the United States, has expanded to other countries, not Indonesia. eSports in Indonesia initially did not receive attention from the government, but slowly transformed into one of the areas that received attention from the government. Indonesia in the eSports ecosystem looks ready for this new field because the country is classified as having aspects that can build an eSports ecosystem that continues to grow, such as internet services, team eSports, game publishers/developers, and the eSports connoisseur community itself. In relation to its very rapid development, the development of eSports certainly requires support from the government, and with that The Indonesian government seeing this potential then made efforts to further develop the existing eSports ecosystem, including inaugurating IeSPA, conducting socialization about eSports, holding eSports matches, establishing PBESI and establishing an eSports academy.